The Subtlety of the Street - Balmat, M Peregrine (Michigan State University Press, 2026)
The Subtlety of the Street examines the effects of small, seemingly mundane words that occur in conversations between street-level workers and those they serve. Combining discourse analysis, public policy studies, and higher education and social work research, M Peregrine Balmat examines data from two distinct ethnographies that comprise over 1100 pages of transcribed social interaction and 24 months of participant observation fieldwork. Balmat uses Interactional Linguistics to examine how responsibility is constructed over time in social work (homeless shelter) and higher education (community college) contexts, bringing to light systemic issues that face street-level disciplines. Analyzing constellations of words—personal pronouns, terms referring to performance benchmarks and assessments, and cultural mythologies—the author shows that clusters of seemingly generic phrases street-level workers use to communicate responsibility can function, in concert, as racialized microaggressions —termed the Gestalt of Responsibility. These problematic linguistic choices can accumulate over a student’s time in the classroom or over a person’s time in shelter. They shift in response to performance assessments and measurements, increasing in unfriendly, morally-loaded constructions of responsibility as testing days and shelter restrictions approach. While street-level research suggests that strategies like these are utilized because workers believe those discourse practices work, the phrases reflect historical English Poor Laws and racialized ideologies leveled against enslaved Black people as well as more modern neoliberal welfare state and education politics where such ideologies persist. The Subtlety of the Street offers recommendations for street-level workers’ collaborative professional development and implications for street-level approaches to pedagogy and practice.